A Study on the Attention of Yoga and Its Development Based on Complex Network Theory - Li, Pengchao; Miao, Qinghong; Meng, Yuchi; Ning, Jie; Long, Jing; Huang, Junya (Frontiers in Physics, 2021)
This research collects data related to yoga in various provinces in China based on the Baidu search index as the data source, and analyzes the public's attention to yoga on the Internet from the perspective of a complex network, so as to dig out characteristics of the people concerned with yoga from 2011 to 2020 and the temporal and spatial change characteristics of yoga attention. Then, this paper is going to transform the time series into the network through the VG model and HVG model, analyze the network characteristics and predict its popularity. Furthermore, the publicity of the project and the public's enthusiasm for the sports project are analyzed based on the combination of the policy, national education level, TV, mobile phone and other communication equipment, so that the market can provide corresponding products and services in a targeted manner and promote the healthy development of the yoga industry.